Building an Asymmetrical Brain: The Molecular Perspective - Schmitz, Judith; Güntürkün, Onur; Ocklenburg, Sebastian (Frontiers in Psychology, 2019)
The brain is one of the most prominent examples for structural and functional differences between the left and right half of the body. For handedness and language lateralization, the most widely investigated behavioral phenotypes, only a small fraction of phenotypic variance has been explained by molecular genetic studies. Due to environmental factors presumably also playing a role in their ontogenesis and based on first molecular evidence, it has been suggested that functional hemispheric asymmetries are partly under epigenetic control. This review article aims at the molecular factors underlying hemispheric asymmetries and their association with inner organ asymmetries. While we previously suggested that epigenetic mechanisms might partly account for the missing heritability of handedness, this article extends this idea by suggesting possible alternatives for transgenerational transmission of epigenetic states that do not require germline epigenetic transmission. This is in line with a multifactorial model of hemispheric asymmetries, integrating genetic, environmental and epigenetic influencing factors in their ontogenesis.